Waterborne acrylic polymer as well as preparation method and application thereof

Through the copolymerization technology of aqueous acrylic polymers, a high-flexible three-dimensional network structure is formed, which solves the problems of high brittleness and rigidity of existing acrylic adhesives, and significantly improves the circulation performance of lithium-ion batteries.

CN119463007APending Publication Date: 2025-02-18SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411428314.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing acrylic binders have problems of high brittleness and rigidity, which is difficult to meet the demand for volume expansion of silicon-based negative electrode materials in lithium-ion batteries, resulting in poor battery circulation performance.

Method used

An aqueous acrylic polymer is developed, which is composed of acrylic acid, a monohydroxyl-containing acrylic compound and a polyhydroxyl-containing acrylic compound to form a highly flexible three-dimensional network structure through neutralization and copolymerization reactions.

Benefits of technology

The binder made of this aqueous acrylic polymer is flexible and has good adhesion, which can effectively resist the volume expansion of the silicon negative electrode and improve the circulation performance of the lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463007A_ABST
    Figure CN119463007A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based acrylic polymer as well as a preparation method and application thereof. The water-based acrylic polymer is prepared by copolymerizing the following monomers in percentage by mass: 35-80% of acrylic acid; 10%-58% of an acrylic acid compound containing a monohydroxyl group; and 2%-10% of an acrylic acid compound containing polyhydroxy. The preparation method of the water-based acrylic polymer comprises the following steps: adding a nitrogen-containing compound aqueous solution into acrylic acid to carry out neutralization reaction until the pH value of the obtained solution is 6-8, and then adding a monohydroxyl-containing acrylic compound, a polyhydroxyl-containing acrylic compound and an initiator to carry out copolymerization reaction to obtain the water-based acrylic polymer. The water-based acrylic polymer is obtained. The acrylic acid binder prepared from the water-based acrylic acid polymer is high in flexibility and good in cohesiveness and can well adapt to high volume expansion of a silicon-based negative electrode when being used as the binder, and a lithium ion battery obtained through final assembly is excellent in cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic adhesives, and in particular to a water-based acrylic polymer and a preparation method and application thereof. Background Art

[0002] Lithium-ion battery is a chemical energy storage device with high energy density (>150Wh / kg), green environmental protection, high safety and stability, and long cycle life. It is widely used in communications, energy storage, transportation and other fields. Silicon-based negative electrode material is a negative electrode material with great development prospects. Its theoretical specific capacity when fully lithiated can reach 4200mAh / g, which is much higher than the currently commonly used commercial graphite material (theoretical specific capacity is 374mAh / g). In addition, as a natural material, silicon material also has the advantages of low price, abundant resources, and green environmental protection. However, silicon-based negative electrode materials will undergo severe volume expansion during the lithiation process. Repeated volume expansion will cause cracking of the negative electrode sheet and even pulverization of silicon particles. At the same time, the solid electrolyte interphase (SEI) is also repeatedly formed during the battery cycle, which will eventually lead to irreversible loss of lithium ions and rapid decay of battery capacity. At present, the volume expansion problem of silicon-based negative electrode materials is mainly solved by nano-engineering (for example: CN 118352507 A porous carbon few-walled carbon nanotube silicon nanocomposite material and preparation and application method) and surface modification (for example: CN 116072841A a method for surface modification of silicon negative electrode material). However, these two methods are not only very complicated to operate, but also very costly, which seriously limits the practical application of silicon-based negative electrode materials.

[0003] Although the amount of binder used in electrode materials is relatively small, it can play a role in resisting stress expansion, maintaining structural stability, improving structural toughness, and optimizing battery structure. Polymer binders with certain flexibility and elasticity can effectively improve the volume expansion of silicon negative electrodes during battery cycles, thereby resisting stress damage to electrodes. Polyacrylic acid (PAA) is a polymer containing a large number of carboxyl groups (-COOH) in its molecular structure. It can form a strong interaction with the silicon surface and has been studied as a silicon negative electrode binder. However, most existing acrylic binders have problems of brittleness and high rigidity, and it is difficult to fully meet the requirements of practical applications.

[0004] Therefore, developing an acrylic binder with high flexibility and good adhesion is of great significance for promoting the large-scale industrial application of silicon-based negative electrode materials. Summary of the invention

[0005] The object of the present invention is to provide a water-based acrylic polymer and a preparation method and application thereof.

[0006] The technical solution adopted by the present invention is:

[0007] A water-based acrylic polymer, which is copolymerized by the following monomers in percentage by mass:

[0008] Acrylic acid: 35% to 80%;

[0009] Acrylic compounds containing monohydroxyl groups: 10% to 58%;

[0010] Polyhydroxy-containing acrylic compounds: 2% to 10%.

[0011] Preferably, the monohydroxyl-containing acrylic compound is at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, and hydroxybutyl acrylate.

[0012] Preferably, the polyhydroxy-containing acrylic compound is at least one of 2,3-dihydroxypropyl acrylate, 2,3-dihydroxypropyl methacrylate, N,N-bis(2-hydroxyethyl)methacrylamide and N-trihydroxymethylmethacrylamide.

[0013] A method for preparing the water-based acrylic polymer as described above comprises the following steps: adding an aqueous solution of a nitrogen-containing compound to acrylic acid for neutralization reaction until the pH value of the obtained solution is 6 to 8, and then adding a monohydroxyl-containing acrylic compound, a polyhydroxyl-containing acrylic compound and an initiator for copolymerization reaction to obtain a water-based acrylic polymer.

[0014] Preferably, the nitrogen-containing compound is at least one of ammonia, ethanolamine, triethylamine, triethylenediamine and pyridine.

[0015] Preferably, the concentration of the nitrogen-containing compound aqueous solution is 0.01 mol / L to 1 mol / L.

[0016] Preferably, the neutralization reaction is carried out at a temperature of 0°C to 5°C.

[0017] Preferably, the initiator is at least one of potassium persulfate, ammonium persulfate, and azobisisobutylamidine hydrochloride.

[0018] Preferably, the amount of the initiator used is 0.1% to 0.5% of the total mass of acrylic acid, the monohydroxyl-containing acrylic compound and the polyhydroxyl-containing acrylic compound.

[0019] Preferably, the copolymerization reaction is carried out at a temperature of 50° C. to 80° C., and the reaction time is 6 h to 48 h.

[0020] Preferably, the copolymerization reaction is carried out in a protective atmosphere with stirring.

[0021] A binder comprising the above-mentioned water-based acrylic polymer.

[0022] Preferably, the binder is an aqueous acrylic polymer solution.

[0023] Preferably, the aqueous acrylic polymer solution has a solid content of 10% to 30%.

[0024] A negative electrode sheet comprises the above-mentioned binder.

[0025] Preferably, the negative electrode sheet comprises silicon particles, a conductive agent and a binder.

[0026] Further preferably, the negative electrode sheet comprises the following components in percentage by mass:

[0027] Silicon particles: 60% to 80%;

[0028] Conductive agent: 10% to 20%;

[0029] Binder: 10%~20%.

[0030] Preferably, the conductive agent is at least one of conductive carbon black, graphene and carbon nanotubes.

[0031] A lithium ion battery comprises the negative electrode sheet.

[0032] The beneficial effects of the present invention are as follows: the acrylic binder made of the water-based acrylic polymer of the present invention has high flexibility and good adhesion. Using it as a binder can well adapt to the high volume expansion of the silicon-based negative electrode, and the lithium-ion battery finally assembled has excellent cycle performance.

[0033] Specifically:

[0034] 1) The aqueous acrylic polymer of the present invention has a highly flexible three-dimensional network structure, which can effectively resist the volume expansion of the silicon negative electrode during the process of lithium extraction / insertion, which not only helps to maintain the structural integrity of the electrode, but also improves the cycle performance of the battery;

[0035] 2) In the preparation process of the water-based acrylic polymer, the present invention uses nitrogen-containing compounds (which will form ammonium ions) to neutralize acrylic acid. Compared with the traditional method of using metal ions for neutralization, the interaction between chain segments is reduced, so that the chain segments can be stretched to a greater extent, thereby being able to introduce hydroxyl-containing monomers to the greatest extent for reaction, which helps to form multiple hydrogen bonds with the carboxyl groups on acrylic acid, and ultimately a highly flexible three-dimensional network structure can be constructed. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1These are SEM images of the negative electrode sheets in Example 1 and Comparative Example 1 before and after the cycle test. DETAILED DESCRIPTION

[0037] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0038] Embodiment 1:

[0039] A water-based acrylic polymer, the preparation method of which is as follows:

[0040] 10 g of acrylic acid was placed in an ice-water bath, and 0.5 mol / L ammonia water was added dropwise while stirring until the pH value of the obtained solution reached 7. The obtained reaction solution was then transferred to a three-necked flask equipped with a condensation reflux device, and 7 g of hydroxyethyl acrylate, 1.5 g of N-trimethylolmethyl acrylamide and 100 g of deionized water were added and stirred evenly. 0.085 g of azobisisobutyramidine hydrochloride was then added, and the mixture was evacuated and filled with nitrogen for 3 times. The mixture was heated to 55° C. and stirred for reaction for 24 h. The mixture was naturally cooled to room temperature to obtain a reaction solution containing an aqueous acrylic polymer. The product was then separated to obtain an aqueous acrylic polymer.

[0041] A binder, the preparation method of which is as follows:

[0042] The reaction solution of the aqueous acrylic polymer is diluted with deionized water until the solid content is 10%, thereby obtaining a binder.

[0043] A negative electrode sheet, the preparation method of which is as follows:

[0044] Silicon particles (particle size of about 150nm), conductive carbon black Super P and the above-mentioned binder are dispersed in deionized water to form a slurry, the mass ratio of silicon particles, conductive carbon black Super P and the aqueous acrylic polymer in the binder is 8:1:1, and then the slurry is coated on a copper foil and dried to obtain a negative electrode sheet.

[0045] Embodiment 2:

[0046] A water-based acrylic polymer, the preparation method of which is as follows:

[0047] 10 g of acrylic acid was placed in an ice water bath, and a triethylenediamine-ammonia solution having a concentration of 0.1 mol / L of triethylenediamine and ammonia was added dropwise with stirring until the pH value of the obtained solution reached 7.5. The obtained reaction solution was transferred to a three-necked flask equipped with a condensation reflux device, and 2.6 g of hydroxyethyl methacrylate, 0.32 g of 2,3-dihydroxypropyl methacrylate and 100 g of deionized water were added and stirred evenly. 0.013 g of potassium persulfate was added, and the mixture was evacuated and filled with nitrogen for 3 times. The mixture was heated to 65° C. and stirred for 6 h. The mixture was naturally cooled to room temperature to obtain a reaction solution containing an aqueous acrylic polymer. The product was separated to obtain an aqueous acrylic polymer.

[0048] A binder, the preparation method of which is as follows:

[0049] The reaction solution of the aqueous acrylic polymer is diluted with deionized water until the solid content is 10%, thereby obtaining a binder.

[0050] A negative electrode sheet, the preparation method of which is as follows:

[0051] Silicon particles (particle size of about 150nm), conductive carbon black Super P and the above-mentioned binder are dispersed in deionized water to form a slurry, the mass ratio of silicon particles, conductive carbon black Super P and the aqueous acrylic polymer in the binder is 8:1:1, and then the slurry is coated on a copper foil and dried to obtain a negative electrode sheet.

[0052] Embodiment 3:

[0053] A water-based acrylic polymer, the preparation method of which is as follows:

[0054] 10 g of acrylic acid was placed in an ice-water bath, and a 1 mol / L triethylamine solution was added dropwise while stirring until the pH value of the obtained solution reached 7.5. The obtained reaction solution was transferred to a three-necked flask equipped with a condensation reflux device, and 15 g of hydroxypropyl acrylate, 1.72 g of N, N-bis(2-hydroxyethyl)methacrylamide and 100 g of deionized water were added and stirred evenly. 0.078 g of azobisisobutyramidine hydrochloride was added, and the mixture was evacuated and filled with nitrogen for 3 times. The mixture was heated to 50° C. and stirred for 48 hours. The mixture was naturally cooled to room temperature to obtain a reaction solution containing an aqueous acrylic polymer. The product was separated to obtain an aqueous acrylic polymer.

[0055] A binder, the preparation method of which is as follows:

[0056] The reaction solution of the aqueous acrylic polymer is diluted with deionized water until the solid content is 10%, thereby obtaining a binder.

[0057] A negative electrode sheet, the preparation method of which is as follows:

[0058] Silicon particles (particle size of about 150nm), conductive carbon black Super P and the above-mentioned binder are dispersed in deionized water to form a slurry, the mass ratio of silicon particles, conductive carbon black Super P and the aqueous acrylic polymer in the binder is 8:1:1, and then the slurry is coated on a copper foil and dried to obtain a negative electrode sheet.

[0059] Embodiment 4:

[0060] A water-based acrylic polymer, the preparation method of which is as follows:

[0061] 10 g of acrylic acid was placed in an ice-water bath, and an ethanolamine-pyridine solution having a concentration of 0.01 mol / L of ethanolamine and pyridine was added dropwise while stirring until the pH value of the obtained solution reached 8. The obtained reaction solution was transferred to a three-necked flask equipped with a condensation reflux device, and 8.6 g of hydroxybutyl acrylate, 1.05 g of N-trimethylolmethyl acrylamide and 100 g of deionized water were added and stirred evenly. 0.038 g of ammonium persulfate was added, and the mixture was evacuated and filled with nitrogen for 3 times. The mixture was heated to 80° C. and stirred for 12 h. The mixture was naturally cooled to room temperature to obtain a reaction solution containing an aqueous acrylic polymer. The product was separated to obtain an aqueous acrylic polymer.

[0062] A binder, the preparation method of which is as follows:

[0063] The reaction solution of the aqueous acrylic polymer is diluted with deionized water until the solid content is 10%, thereby obtaining a binder.

[0064] A negative electrode sheet, the preparation method of which is as follows:

[0065] Silicon particles (particle size of about 150nm), conductive carbon black Super P and the above-mentioned binder are dispersed in deionized water to form a slurry, the mass ratio of silicon particles, conductive carbon black Super P and the aqueous acrylic polymer in the binder is 8:1:1, and then the slurry is coated on a copper foil and dried to obtain a negative electrode sheet.

[0066] Embodiment 5:

[0067] A water-based acrylic polymer, the preparation method of which is as follows:

[0068] 10 g of acrylic acid was placed in an ice water bath, and a 0.5 mol / L pyridine solution was added dropwise while stirring until the pH value of the obtained solution was 7. The obtained reaction solution was transferred to a three-necked flask equipped with a condensation reflux device, and 10 g of hydroxypropyl methacrylate, 0.58 g of 2,3-dihydroxypropyl acrylate and 100 g of deionized water were added and stirred evenly. 0.041 g of ammonium persulfate was added, and the mixture was evacuated and filled with nitrogen for 3 times. The mixture was heated to 60° C. and stirred for 36 hours. The mixture was naturally cooled to room temperature to obtain a reaction solution containing an aqueous acrylic polymer, and the product was separated to obtain an aqueous acrylic polymer.

[0069] A binder, the preparation method of which is as follows:

[0070] The reaction solution of the aqueous acrylic polymer is diluted with deionized water until the solid content is 10%, thereby obtaining a binder.

[0071] A negative electrode sheet, the preparation method of which is as follows:

[0072] Silicon particles (particle size of about 150nm), conductive carbon black Super P and the above-mentioned binder are dispersed in deionized water to form a slurry, the mass ratio of silicon particles, conductive carbon black Super P and the aqueous acrylic polymer in the binder is 8:1:1, and then the slurry is coated on a copper foil and dried to obtain a negative electrode sheet.

[0073] Comparative Example 1:

[0074] A water-based acrylic polymer, the preparation method of which is as follows:

[0075] 10 g of acrylic acid was placed in an ice-water bath, and a 0.5 mol / L sodium hydroxide solution was added dropwise while stirring until the pH value of the obtained solution reached 7. The obtained reaction solution was then transferred to a three-necked flask equipped with a condensation reflux device, and 7 g of hydroxyethyl acrylate, 1.5 g of N-trimethylolmethyl acrylamide and 100 g of deionized water were added and stirred evenly. 0.085 g of azobisisobutyramidine hydrochloride was then added, and the mixture was evacuated and filled with nitrogen for 3 times. The mixture was heated to 55° C. and stirred for reaction for 24 h. The mixture was naturally cooled to room temperature to obtain a reaction solution containing an aqueous acrylic polymer. The product was then separated to obtain an aqueous acrylic polymer.

[0076] A binder, the preparation method of which is as follows:

[0077] The reaction solution of the aqueous acrylic polymer is diluted with deionized water until the solid content is 10%, thereby obtaining a binder.

[0078] A negative electrode sheet, the preparation method of which is as follows:

[0079] Silicon particles (particle size of about 150nm), conductive carbon black Super P and the above-mentioned binder are dispersed in deionized water to form a slurry, the mass ratio of silicon particles, conductive carbon black Super P and the aqueous acrylic polymer in the binder is 8:1:1, and then the slurry is coated on a copper foil and dried to obtain a negative electrode sheet.

[0080] Comparative Example 2:

[0081] A water-based acrylic polymer, the preparation method of which is as follows:

[0082] Place 10 g of acrylic acid in an ice-water bath, and then add a 0.5 mol / L lithium hydroxide solution dropwise while stirring until the pH value of the obtained solution is 7. Transfer the obtained reaction solution to a three-necked flask equipped with a condensation reflux device, add 15 g of hydroxypropyl acrylate, 1.72 g of N,N-bis(2-hydroxyethyl)methacrylamide and 100 g of deionized water and stir evenly, then add 0.078 g of azobisisobutylamidine hydrochloride, evacuate and fill with nitrogen for 3 times, heat to 55°C and stir to react for 24 hours, and cool naturally to room temperature (the reaction system is severely gelled and deionized water cannot be added for dilution, so the binder cannot be obtained. The reason is that: there is a strong interaction between the metal ions and the carboxylate ions, the stretching of the chain segments is restrained, and when a higher proportion of polyhydroxy monomers is introduced, the chain segments are excessively entangled, which eventually leads to gelation of the system).

[0083] Performance Test:

[0084] 1) The water-based acrylic polymers in Examples 1 to 5 and Comparative Example 1 were subjected to differential scanning calorimetry (DSC) testing, and the negative electrode sheets in Examples 1 to 5 and Comparative Example 1 were subjected to peeling force testing (the testing process was as follows: the negative electrode sheet was cut into rectangular strips with a size of 40 mm×25 mm, and a double-sided tape with a width of 25 mm was attached to one end of a glass slide with a size of 76 mm×25 mm, and then the copper foil surface of the strip was attached to the double-sided tape, and a 3M tape with a width of 19 mm was attached to the coated surface of the strip, and then stretched and peeled, and the stretching speed was 60 mm / min). The glass transition temperature of the water-based acrylic polymer and the peeling force of the negative electrode sheet obtained by the test are shown in the following table:

[0085] Table 1 Glass transition temperature of waterborne acrylic polymer and peeling force test results of negative electrode sheet

[0086] Test items Glass transition temperature(℃) Peel force(N) Example 1 97 6.44 Example 2 102 4.17 Example 3 83 5.90 Example 4 106 4.85 Example 5 90 6.09 Comparative Example 1 121 6.42

[0087] From Table 1, we can see that:

[0088] a) The peeling forces of the negative electrode sheets in Examples 1 to 5 and Comparative Example 1 are all within the range that can meet normal use requirements;

[0089] b) The glass transition temperature of the water-based acrylic polymers in Examples 1 to 5 is significantly lower than that in Comparative Example 1, indicating that the polymer chain segments are more flexible. The reason is that in the aqueous solution system, the electrostatic repulsion between the metal ions bound to the carboxylic acid groups in acrylic acid is greater than that of ammonium ions. The large electrostatic repulsion will prevent the polymer chain segments from unfolding, severely restricting the movement of the polymer chain segments, thereby reducing the flexibility of the polymer. The weak electrostatic repulsion of ammonium ions can effectively alleviate this phenomenon, thereby improving the flexibility of the polymer.

[0090] 2) The binders in Examples 1 to 5 and Comparative Example 1 were injected into a mold to cast into film strips with a size of 6 cm×1 cm, and then subjected to a tensile performance test at a tensile rate of 50 mm / min. The tensile performance test results of the obtained film strips are shown in the following table:

[0091] Table 2 Tensile properties test results of film specimens

[0092] Test items Stress(MPa) strain(%) Example 1 23 18.2 Example 2 25 10.4 Example 3 29 24.5 Example 4 31 9.3 Example 5 29 21.9 Comparative Example 1 16 0.5

[0093] It can be seen from Table 2 that the stress and strain of the film strips made of the binders in Examples 1 to 5 are significantly higher than those of the film strips made of the binder in Comparative Example 1, indicating that the binders in Examples 1 to 5 are more flexible. The reason is that the ammonium ions formed by the neutralization reaction of the nitrogen-containing compound with acrylic acid can effectively limit the hydrogen bond interaction between the carboxylic acid group and the hydroxyl group, inhibit the occurrence of the gelation reaction, and enable more flexible monomers to participate in free radical polymerization, which can reduce the glass transition temperature of the polymer to a greater extent and improve the flexibility of the polymer.

[0094] 3) The surface morphology of the negative electrode sheets in Example 1 and Comparative Example 1 was tested by scanning electron microscopy (SEM), and then the negative electrode sheets were assembled into a CR2025 button half-cell in the order of positive electrode shell, negative electrode sheet, electrolyte, separator, electrolyte, lithium sheet, and negative electrode shell in a glove box. The half-cell was activated (0.05C activation for 1 cycle, 0.1C activation for 3 cycles), and then a cycle test was performed (0.2C cycle for 150 cycles). The surface morphology of the negative electrode sheet after the cycle test was tested by scanning electron microscopy. The SEM images of the obtained negative electrode sheet before and after the cycle test are as follows: Figure 1 (a, c, e and g in the figure are before the cycle test, and b, d, f and h are after the cycle test).

[0095] Depend on Figure 1It can be seen that the expansion rate of the cross section of the negative electrode sheet in Comparative Example 1 is as high as 264%, and obvious cracks appear on the surface of the negative electrode sheet, while the expansion rate of the cross section of the negative electrode sheet in Example 1 is only 80.4%, and the negative electrode sheet still maintains structural integrity, indicating that the acrylic binder made of the water-based acrylic polymer of the present invention can well adapt to the high volume expansion of the silicon-based negative electrode, and the lithium-ion battery finally assembled has excellent cycle performance.

[0096] In addition, through the same test, it was found that the negative electrode sheets in Examples 2 to 5 also have a low expansion rate (≤110%), and the negative electrode sheets can also maintain structural integrity after 150 cycles of testing.

[0097] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A water-based acrylic polymer, characterized in that It is copolymerized by the following monomers in percentage by mass: Acrylic acid: 35% to 80%; Acrylic compounds containing monohydroxyl groups: 10% to 58%; Polyhydroxy-containing acrylic compounds: 2% to 10%.

2. The aqueous acrylic polymer according to claim 1, characterized in that: The monohydroxyl-containing acrylic compound is at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, and hydroxybutyl acrylate.

3. The aqueous acrylic polymer according to claim 1 or 2, characterized in that: The polyhydroxy-containing acrylic compound is at least one of 2,3-dihydroxypropyl acrylate, 2,3-dihydroxypropyl methacrylate, N,N-bis(2-hydroxyethyl)methacrylamide and N-trihydroxymethylmethacrylamide.

4. A method for preparing a waterborne acrylic polymer according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: adding an aqueous solution of a nitrogen-containing compound into acrylic acid for neutralization reaction until the pH value of the obtained solution is 6-8, and then adding an acrylic compound containing a monohydroxyl group, an acrylic compound containing a polyhydroxyl group and an initiator for copolymerization reaction to obtain a water-based acrylic polymer.

5. The preparation method according to claim 4, characterized in that: The nitrogen-containing compound is at least one of ammonia, ethanolamine, triethylamine, triethylenediamine and pyridine; the initiator is at least one of potassium persulfate, ammonium persulfate and azobisisobutyramidine hydrochloride.

6. The preparation method according to claim 4 or 5, characterized in that: The amount of the initiator used is 0.1% to 0.5% of the total mass of acrylic acid, acrylic compounds containing monohydroxyl groups and acrylic compounds containing polyhydroxyl groups.

7. The preparation method according to claim 4 or 5, characterized in that: The copolymerization reaction is carried out at a temperature of 50° C. to 80° C., and the reaction time is 6 h to 48 h.

8. A binder, characterized in that: The aqueous acrylic polymer according to any one of claims 1 to 3 is included.

9. A negative electrode sheet, characterized in that: Contains the binder according to claim 8.

10. A lithium ion battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Silicon negative electrode material surface modification method

    CN116072841A

  • Porous carbon few-walled carbon nanotube silicon nano composite material and preparation and application methods thereof

    CN118352507A

  • Negative electrode paste, negative electrode, and rechargeable battery

    CN114430028A

  • Negative electrode active material layer for lithium ion secondary batteries and lithium ion secondary battery

    JP2015103449A

  • Binder for electrode of secondary battery that comprises secondary battery negative electrode containing silicon-based active material, and use of same

    WO2024034442A1

Cited By

  • High-stripping-degree water-based acrylic resin binder as well as preparation method and application thereof

    CN120590888A